(untitled) (DAPesquisa, 2025)
To ensure the success of fashion events, organization is essential. The objective of this research is to identify the types of fashion events and indicate the necessary steps for their organization. Qualitative, descriptive research was applied, with technical procedures for data collection and bibliographic research. Qualitative data analysis was performed to interpret the results. The results indicated that fashion events are divided into Trade Shows, Fashion Salons, Fairs, and Fashion Shows, each aimed at a specific audience. The results also include the professionals who can be part of the teams and the steps for organizing fashion events.